Capacity of roadway infrastructure and its relation with functional urban regions - Manzato, Gustavo Garcia [UNESP]; Dias, Rodrigo Sanches [UNESP]; Da Silva, Antônio Nélson Rodrigues (My University, 2015)
This study proposes a roadway infrastructure supply index that considers road capacity for the analysis of its relation with the metropolization process. An exploratory analysis using ESDA (Exploratory Spatial Data Analysis) techniques was conducted in São Paulo state for comparing the index values if calculated with and without road capacity data. The results suggest that the identification of homogeneous urban regions is improved when such data are considered. Therefore, the inclusion of qualitative characteristics has not only contributed to the determination of the index, but also made clear they significantly reflect the intense interactions among the municipalities of a region.